Modelos matemáticos aplicados a curva de crescimento e deposição de nutrientes em coelhos - Silva, Jordanio Fernandes da (2017)
The rapid rate of growth in animals at the beginning of life can be accompanied by several problems of metabolic, skeletal, and may even compromise the life of the animal. And in view of the scarcity of these studies in rabbit breeding, the aim of this article is to evaluate the growth curves of White New Zealand rabbits. For this, we used weekly weighing data of 274 White New Zealand rabbits, with an initial average weight of 0,052 ± 0,009 kilograms, originating from 40 matrices, reared in a cage confined in metal, receiving water and food ad libitum, with mixed diet formulated to meet the nutritional requirements of the animals in the growth and reproduction phases. The collected data were submitted to the mathematical models of Gompertz, Logistic, Quadratic polynomial exponential and Logarithmic quadratic to estimate asymptotic weight and maturation rate. The parameters of the models were estimated by the Gauss-Newton method using the NLIN procedure of SAS. The criteria used to select the model for the growth curve were mean square of the residual, determination coefficient, mean absolute deviation of the residues, and residual distribution graphics. After choosing the best model, the absolute growth rate was calculated using the Gompertz equation. The results showed that the Gompertz model was the most adequate to describe the growth curves taking into account all parameters evaluated in this study and that the logistic model was the most efficient to estimate the deposition curves in rabbits. The Gompertz model presents a higher adjustment quality to the growth curves, estimating the inflection point at 49 days of age with daily gain of 26 grams.